2010
DOI: 10.1002/ps.1989
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐resistance relationships between neonicotinoids and pymetrozine in Bemisia tabaci (Hemiptera: Aleyrodidae)

Abstract: Cross-resistance between neonicotinoids and pymetrozine in B. tabaci probably reflects the overexpression of a cytochrome-P450-dependent monooxygenase capable of metabolising both types of compound in spite of their apparent structural dissimilarity. Given the predominance of this mechanism in B. tabaci, both can contribute to resistance management but should be placed within the same treatment 'window'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
67
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 25 publications
8
67
2
2
Order By: Relevance
“…Gorman et al 12) have found that cytochrome P450 may be the major cause of the cross-resistance between neonicotinoids and pymetrozine in Bemisia tabaci. The important metabolic detoxification of CarE for other insecticides such as pyrethroids, organophosphates, and carbamates, has also been proven in the cotton aphid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gorman et al 12) have found that cytochrome P450 may be the major cause of the cross-resistance between neonicotinoids and pymetrozine in Bemisia tabaci. The important metabolic detoxification of CarE for other insecticides such as pyrethroids, organophosphates, and carbamates, has also been proven in the cotton aphid.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] In addition, cross-resistance between neonicotinoids and other groups of insecticides has been investigated in several pests. 12,13) Neonicotinoid insecticides, including imidacloprid, have replaced pyrethroids, chlorinated hydrocarbons, organophosphates, carbamates, and several other classes of insecticides and have become the primary insecticide for A. gossypii control in China with high effectiveness. 14) However, increasingly, problems of A. gossypii resistance to imidacloprid have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The major mechanism involved in neonicotinoid resistance is metabolic detoxification with increase in cytochrome P450 and esterases in many insect pests [29][30][31]. However, the mechanism of nitenpyram resistance in green lacewing is not reported worldwide.…”
Section: Introductionmentioning
confidence: 95%
“…Pymetrozine is a pyridine azomethine antifeedant insecticide that is unrelated to the neonicotinoids structurally and functionally. However resistance to pymetrozine and neonicotinoids in B. tabaci is primarily due to the same mechanism [35]. Evidence of cross resistance between neonicotinoids and pymetrozine [35] and the example of whiteflies exposed only to acetamiprid developing resistance to thiamethoxam [22] illustrate the potential of B. tabaci to develop tolerance to an active ingredient to which it has not been exposed.…”
Section: Discussionmentioning
confidence: 99%